Model Komunikasi Pimpinan Dalam Meningkatkan Disiplin Kerja Pegawai Pada PT. Malindo Feedmill, Tbk Desa Sembawa Banyuasin - Wijaya, Ario Dendi; Alhaq, Muh. Nato; Iman, Asrul Nur (Jurnal Publisitas, 2020)
This study aims to see and examine the leadership communication model in improving employee work discipline at PT. Malindo Feedmill Tbk, Sembawa Village, Sembawa District, Banyuasin III Regency, with a sample size of 75 people. The research method used in this research is quantitative with the aim of knowing the leadership communication model in improving the work discipline of employees at PT. Malindo Feedmill, Tbk using the product map formula, while the research instrument for obtaining data in the field is a school questionnaire that is created and developed by the author himself based on the development of relevant theories with research variables and research indicators. Trying to provide an overview of what is there, by researching, then analyzing it to find related problems. The results of calculations using the current product formula to see the leadership communication model in improving the work discipline of employees of PT. Malindo Feedmill Tbk in Sembawa Village, Sembawa District, Banyuasin III Regency is 0.769, while the determinant r (r2) is 59.13%, the remaining is 40.87%; by other factors not examined in this study.